Robust Control Approach for Volterra Models - Biagiola, Silvina Ines (2016)
Recently, different algorithms for identification of several uncertain nonlinear models, referred to as Volterra-type models, were introduced in the literature. This work deals with the development of a suitable robust model predictive control (MPC) scheme able to cope with the uncertain characterization of those types of models. A discrete-time multivariable algorithm with efficient computational performance is developed. A simulation example based on a multivariable distillation column is introduced to illustrate the behavior of this methodology under the presence of uncertainties and constraints on the manipulated and controlled variables.